SRC Family Kinase Inhibition Through a New Pyrazolo[3, 4‐d]Pyrimidine Derivative as a Feasible Approach for Glioblastoma Treatment. Issue 5 (May 2015) - Ceccherini, Elisa; Indovina, Paola; Zamperini, Claudio; Dreassi, Elena; Casini, Nadia; Cutaia, Ornella; Forte, Iris Maria; Pentimalli, Francesca; Esposito, Luca; Polito, Maria Sole; Schenone, Silvia; Botta, Maurizio; et al.
ABSTRACT Glioblastoma (GB) is the most common and aggressive primary tumor of the central nervous system. The current standard of care for GB consists of surgical resection, followed by radiotherapy combined with temozolomide chemotherapy. However, despite this intensive treatment, the prognosis remains extremely poor. Therefore, more effective therapies are urgently required. Recent studies indicate that SRC family kinases (SFKs) could represent promising molecular targets for GB therapy. Here, we challenged four GB cell lines with a new selective pyrazolo[3, 4‐d]pyrimidine derivative SFK inhibitor, called SI221. This compound exerted a significant cytotoxic effect on GB cells, without significantly affecting non‐tumor cells (primary human skin fibroblasts), as evaluated by MTS assay. We also observed that SI221 was more effective than the well‐known SFK inhibitor PP2 in GB cells. Notably, despite the high intrinsic resistance to apoptosis of GB cells, SI221 was able to induce this cell death process in all the GB cell lines, as observed through cytofluorimetric analysis and caspase‐3 assay. SI221 also exerted a long‐term inhibition of GB cell growth and was able to reduce GB cell migration, as shown by clonogenic assay and scratch test, respectively. Moreover, through in vitro pharmacokinetic assays, SI221 proved to have a high metabolic stability and a good potential to cross the blood brain barrier, which is an essential requirement for a drug intended to treat brain tumors. Therefore, despite the need of developing strategies to improve SI221 solubility, our results suggest a potential application of this selective SFK inhibitor in GB therapy. J. Cell. Biochem. 116: 856–863, 2015. © 2014 Wiley Periodicals, Inc.